Antimicrobial Use in US Hospitals: Comparison of Results From Emerging Infections Program Prevalence Surveys, 2015 and 2011. (10th June 2020) - Magill, Shelley S; O'Leary, Erin; Ray, Susan M; Kainer, Marion A; Evans, Christopher; Bamberg, Wendy M; Johnston, Helen; Janelle, Sarah J; Oyewumi, Tolulope; Lynfield, Ruth; Rainbow, Jean; Warnke, Linn; et al.
Abstract: Background: In the 2011 US hospital prevalence survey of healthcare-associated infections and antimicrobial use 50% of patients received antimicrobial medications on the survey date or day before. More hospitals have since established antimicrobial stewardship programs. We repeated the survey in 2015 to determine antimicrobial use prevalence and describe changes since 2011. Methods: The Centers for Disease Control and Prevention's Emerging Infections Program sites in 10 states each recruited ≤25 general and women's and children's hospitals. Hospitals selected a survey date from May–September 2015. Medical records for a random patient sample on the survey date were reviewed to collect data on antimicrobial medications administered on the survey date or day before. Percentages of patients on antimicrobial medications were compared; multivariable log-binomial regression modeling was used to evaluate factors associated with antimicrobial use. Results: Of 12 299 patients in 199 hospitals, 6084 (49.5%; 95% CI, 48.6–50.4%) received antimicrobials. Among 148 hospitals in both surveys, overall antimicrobial use prevalence was similar in 2011 and 2015, although the percentage of neonatal critical care patients on antimicrobials was lower in 2015 (22.8% vs 32.0% [2011]; P = .006). Fluoroquinolone use was lower in 2015 (10.1% of patients vs 11.9% [2011]; P < .001). Third- or fourth-generation cephalosporin use was higher (12.2% vs 10.7% [2011]; P = .002), as was carbapenem use (3.7% vs 2.7% [2011]; P < .001). Conclusions: Overall hospital antimicrobial use prevalence was not different in 2011 and 2015; however, differences observed in selected patient or antimicrobial groups may provide evidence of stewardship impact. Abstract : Approximately half of US hospital inpatients in prevalence surveys conducted in 2011 and 2015 were on antimicrobial medications. Changes in antimicrobial use in selected inpatient locations and in the use of selected antimicrobial medications may provide evidence of stewardship impact.